2007
DOI: 10.1080/17453670710014626
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of shoulder arthrodesis performed with plate fixation: 18 patients examined after 3–15 years

Abstract: Background and purpose There have been few reports on the long-term function after shoulder arthrodesis. We report the outcome after shoulder arthrodesis with plate fixation in 18 patients who were followed for 3-15 years.Methods 25 patients with a median age of 64 (19-75) years were operated with a shoulder arthrodesis between 1982 and 2003. Standard AO surgical technique with plating was used in all patients. 18 of the patients were examined retrospectively after a mean of 8 (3-15) years. 6 of the other pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
1
18
1
2
Order By: Relevance
“…The values are within the same range as reported by Esenyel et al, whose patients attained 35.9 points [19]. Both Dimme et al and Tharangajah et al reported values of 32 points [2,5]. The SSV compares the diseased or operated shoulder with a fully healthy shoulder, which is given a value of 100 % [14].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The values are within the same range as reported by Esenyel et al, whose patients attained 35.9 points [19]. Both Dimme et al and Tharangajah et al reported values of 32 points [2,5]. The SSV compares the diseased or operated shoulder with a fully healthy shoulder, which is given a value of 100 % [14].…”
Section: Discussionsupporting
confidence: 83%
“…Depending on the surgical procedure, this may be as common as 40 %, and secondary correction of the position may sometimes be necessary [2,4,17,18,30]. Other complications in- clude infections, periarticular fractures, painful implant conflicts, and malposition [2,19]. There are also published reports of neural lesions, haematomas, pneumothorax, implant fracture, and CRPS (complex regional pain syndrome) [4].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative infections have been reported in 0~14% of shoulder arthrodeses [7,9,15,19]. In our cases, we routinely used prophylactic antibiotics and did not experience any infections.…”
Section: Discussionmentioning
confidence: 95%
“…Among the salvage procedures that can be performed are resection arthroplasty, conversion to hemiarthroplasty, and arthrodesis; however, these alternatives do not reliably decrease pain and restore function to the affected shoulder. 4,6,15 As an alternative, reverse shoulder arthroplasty (RSA) has been considered as another treatment option for failed TSA. RSA has been shown to be an effective treatment for other complex shoulder problems, including rotator cuff arthropathy, 21,23 failed hemiarthroplasty, 12 and proximal humerus fractures.…”
mentioning
confidence: 99%